2020
DOI: 10.1038/s41598-020-77655-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of hyaluronic acid degradation on the regulation of human astrocyte phenotype using multicomponent interpenetrating polymer networks (mIPNs)

Abstract: Hyaluronic acid (HA) is a highly abundant component in the extracellular matrix (ECM) and a fundamental element to the architecture and the physiology of the central nervous system (CNS). Often, HA degradation occurs when an overreactive inflammatory response, derived from tissue trauma or neurodegenerative diseases such as Alzheimer’s, causes the ECM in the CNS to be remodeled. Herein, we studied the effects of HA content as a key regulator of human astrocyte (HAf) reactivity using multicomponent interpenetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
2
11
1
Order By: Relevance
“…On the other hand, ECM hydrogels with a low HA content (6-6-5, 12-6-5) showed significant increases in cell metabolic activity with time (p < 0.05; Figure 4) and supported extensive cell spreading, which is indicative of good cell viability (Figure 5). These results agree with prior studies that employed comparable compositions of collagen and HA to form mIPN hydrogels, and suggests that collagen provides the essential cell binding sites to promote cell adhesion, spreading, and proliferation [14,15]. Apart from the ECM composition, substrate stiffness is also known to have a profound effect on cell morphology, growth, and phenotype via the modulation of the mechanosensing pathways [22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, ECM hydrogels with a low HA content (6-6-5, 12-6-5) showed significant increases in cell metabolic activity with time (p < 0.05; Figure 4) and supported extensive cell spreading, which is indicative of good cell viability (Figure 5). These results agree with prior studies that employed comparable compositions of collagen and HA to form mIPN hydrogels, and suggests that collagen provides the essential cell binding sites to promote cell adhesion, spreading, and proliferation [14,15]. Apart from the ECM composition, substrate stiffness is also known to have a profound effect on cell morphology, growth, and phenotype via the modulation of the mechanosensing pathways [22].…”
Section: Discussionsupporting
confidence: 88%
“…While age-related changes in brain ECM properties have been implicated in the onset and progression of neurodegenerative diseases such as AD, little is known about the role of specific ECM properties (composition, stiffness, and their interplay) on cellular level changes that may trigger the disease [11]. Although prior studies have reported on the impact of modulating the composition of specific ECM components such as HA and Matrigel on astrocytes [14,15], there is a need for a systematic investigation of the combined effects of ECM composition and stiffness on the astrocyte response to better understand the role of the ECM in brain function. Herein, xeno-free biomimetic hydrogel-based ECM models comprising collagen and HA (the backbone of the brain ECM) were employed and the impact of changes in the ECM composition and ECM stiffness on astrocyte cell morphology, proliferation, and phenotype was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, HA has been shown to reduce the number of astrocytes after brain damage [56]. The slightly better performance of 5% MeHA over 3% MeHA may coincide with a recent study on the role of HA in brain injury and neurodegenerative disease, which concluded that a lesser amount of high molecular weight HA is related with greater astrocyte reactivity and inflammation [57]. It will be relevant to explore how the host response differs in brains lesioned to simulate PD.…”
Section: Discussionmentioning
confidence: 96%
“… 8 Hyaluronic acid (HA) is a crucial component of the central nervous system and a scaffold component of the extracellular matrix (CNS). 9 It also modulates intercellular signaling through interactions with Hyaluronan neuronal cell surface receptors like Cluster of Differentiation 44 (CD44), Hyaluronan-mediated motility (RHAMM), and Intercellular adhesion molecule 1 (ICAM). 10 The degradation of hyaluronic acid as a result of an excessive inflammatory response brought on by tissue trauma and neurodegenerative disease leads to the remodeling of ECM of the nervous system.…”
Section: Introductionmentioning
confidence: 99%